Effect of binaural beat brainwave entrainment on brainwave ratios in students with learning difficulties - Kanhere Banait, Shweta; Ranjan, Prabhat; More, Rajendra (Institute of Advanced Engineering and Science, 2025)
This study examined the impact of binaural beat brainwave entrainment (BB BWE) on cognitive function and learning performance (LP) in children aged 8-13 with learning difficulties. A group of 52 participants was divided into a test group (TG) receiving BB BWE for four weeks and a control group (CG) without intervention. Results showed significant improvements in the TG, with LP increasing by up to 78% by week 4 according to cognitive assessment methods. EEG data corroborated these findings, showing a 74% improvement in TG students’ performance. Favorable changes in Electroencephalography (EEG) ratios were observed, including decreased theta/beta and theta/alpha ratios and an increased alpha/beta ratio. Topographical EEG maps revealed more balanced brain activity patterns post-BWE. The CG showed no significant changes. Notably, performance in the TG declined after discontinuing BWE, suggesting the need for ongoing intervention to maintain benefits. These findings indicate that BB BWE could be an effective non-invasive method for enhancing cognitive function and learning capacity in individuals with learning difficulties. However, further research is needed to establish long-term effects and optimal application protocols.